Algorithm school between creativity, collaboration and corporeity - Laura Corazza; Chiara Panciroli; Patrizio Vignola (Firenze University Press, 2020)
This article presents three didactic experiences. These were realised in the primary school and were finalised to achieving a gradual approach to computational thinking through an experimentation with the operative logic of the algorithms. The wealth of the cognitive objectives identified in the three didactic experiences and the use of active learning strategies have shifted the focus from a technical/functional approach to a more social, aesthetic and cultural one, oriented to developing ideational, creative and collaborative competencies.   A scuola di algoritmi tra creatività, collaborazione e corporeità. In questo articolo sono presentate tre esperienze didattiche realizzate nella scuola primaria e finalizzate a un approccio graduale al pensiero computazionale attraverso la sperimentazione della logica operativa degli algoritmi. La ricchezza degli obiettivi cognitivi individuati nelle tre esperienze didattiche e l'utilizzo di strategie per l'apprendimento attivo hanno spostato il focus da un approccio tecnico/funzionale a uno più sociale, estetico e culturale, orientato a sviluppare competenze ideative, creative e collaborative.